Universal Clinic Legal Education: Necessary and Feasible - Robert R. Kuehn (Washington University Journal of Law & Policy, 2017)
This Essay analyzes the data surrounding clinical education in law schools. Kuehn compares the legal education experience to other professional schools, noting that the legal field does not take the steps to prepare law students for the professional field that other schools do. Kuehn argues that a mandated clinical experience for all students is both not costly to obtain and feasible to immediately implement. Kuehn concludes his argument by calling for required clinical training in ABA-approved law schools to ensure practice-ready professionals.
Keywords: clinical education; law school; law students; legal career; legal education; clinical training; ABA; universal clinical education